2020
DOI: 10.1186/s13673-020-00237-7
|View full text |Cite
|
Sign up to set email alerts
|

Don’t click: towards an effective anti-phishing training. A comparative literature review

Abstract: The security threat posed by email-based phishing campaigns targeted at employees is a well-known problem experienced by many organizations. Attacks are reported each year, and a reduction in the number of such attacks is unlikely to occur in the near future (see Fig. 1). A common type of phishing attack involves an attacker attempting to trick victims into clicking on links sent via email. Such links redirect victims to websites that are carefully designed to mimic those of legitimate organizations with the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(43 citation statements)
references
References 109 publications
5
30
0
Order By: Relevance
“…This finding indicated that H2 was supported. It is also in line with previous research (e.g., Bose & Leung, 2008;Arachchilage & Love, 2014;Baral & Arachchilage, 2019;Verkijika, 2019;and Jampen et al, 2020).…”
Section: Discussionsupporting
confidence: 93%
“…This finding indicated that H2 was supported. It is also in line with previous research (e.g., Bose & Leung, 2008;Arachchilage & Love, 2014;Baral & Arachchilage, 2019;Verkijika, 2019;and Jampen et al, 2020).…”
Section: Discussionsupporting
confidence: 93%
“…Besides, the great success of phishing emails in deceiving can be attributed to the fact that phishers become smarter [58]. Therefore, even the tech-savvy people can be deceived, while regular training can certainly shield an organization, as previous works suggest [59,60].…”
Section: Key Findingsmentioning
confidence: 99%
“…Upfront training explains concepts in a dedicated training session. Its effectiveness depends on the user's ability to recall and apply these learned lessons in later situations, which can be challenging since people tend to forget unused information [18,64], necessitating periodical training [34]. Even if they can remember, attackers also continuously adjust their tactics over time, invalidating some of the learned information [5,22].…”
Section: User Trainingmentioning
confidence: 99%